Dental practitioner’s knowledge, opinions and methods of management of oral premalignancy and malignancy - Mohamed Abdullah Jaber (Saudi Dental Journal)
Objectives: The present study outlines the results of a pilot study to determine the knowledge and awareness of a cohort of dentists in United Arab Emirates (UAE) regarding aetiology, clinical features and appropriate early management of oral premalignant and malignant lesions. Materials and methods: A self-administered questionnaire was constructed and posted to 300 UAE Dental Practitoners (DPs), selected randomly from the register of Emirates Dental Association. The present report details the responses of this cohort. Results: 182 questionnaires were completed and returned (response rate 60.6%). One hundred and twenty-seven (69.8%) of the responding dentists were male and the median age of the DPs was 40 years (range 24–75 years). The majority (84%) practised or had practised in or around Dubai and Sharjah, 75% had graduated from a dental school after 1980. Eighty-two respondents (45.0%) had attended specific courses on premalignant or malignant oral lesions. During their undergraduate training 70% of DPs had witnessed more than 10 patients with oral SCC. Only 60.4% of respondents indicated that the tobacco and alcohol use were the principle causes of oral SCC while 19.7% suggested that HIV disease was a risk factor for oral SCC. 29% of DPs routinely recorded the tobacco or alcohol use of their patients and only 3.8% offered advice to patients regarding modification of these habits. Eight-three percent of the respondents suggested that clinical screening was an effective means of reducing the frequency of premalignant and malignant oral lesions. Conclusions: In view of the gradual rise in oral malignancy worldwide there is an increased need for DPs to be able to recognize the signs and symptoms of oral malignancy and premalignancy, provide appropriate preventive advice and be aware of the appropriate early management of patients with such oral lesions. Keywords: Dental practitioners, Knowledge, Malignancy, Premalignancy